1974
DOI: 10.1007/bf00390857
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-methionine-threonine interactions in growth and development of Mimulus cardinalis seedlings

Abstract: Plants of Mimulus cardinalis Douglas (Scrophulariaceae) were grown in axenic culture from seed for 28 days on a minimal salts medium supple-mented with L-lysine, L-methionine, L-threonine, L-isoleucine, DL-or L-homoserine or DL-homocysteine, alone or in combinations ranging from 5 to 1000 μM. Abnormal growth was observed at the higher concentrations of all these aminoacidsexcept homocysteine. The lysine inhibition was significantly reduced by methionine, homocysteine or isoleucine. The threonine inhibition was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The purity and identity of MACC was confirmed by paper chromatography, melting point, and GC-MS; ACC assay (14) revealed that it contained 0.05% of free ACC. This amount of contaminated ACC was insignificant to account for the marked increase in ACC levels shown in Figure 2 and Tables II and III (12), and the radioactivity of the effluents and eluates was determined individually with a scintillation counter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purity and identity of MACC was confirmed by paper chromatography, melting point, and GC-MS; ACC assay (14) revealed that it contained 0.05% of free ACC. This amount of contaminated ACC was insignificant to account for the marked increase in ACC levels shown in Figure 2 and Tables II and III (12), and the radioactivity of the effluents and eluates was determined individually with a scintillation counter.…”
Section: Methodsmentioning
confidence: 99%
“…In 1970 Bryan et al (6) aspartokinase from multicellular plants and demonstrated feedback inhibition as well. The effect of L+T was demonstrated in rice tissue culture (8), in barley (4), in Mimulus seedlings (12), in maize tissue culture (10), and in carrot suspension cultures (7,15). More recently, maize plants were recovered from L+T selections and progeny showed elevated threonine levels (13).…”
mentioning
confidence: 99%
“…In addition, amino acids from unrelated pathways can rescue the plant growth by giving general growth stimulus or reactivating the targeted enzyme in the case of end product of competitive pathways. Active amino acids for plant growth inhibition and plant growth rescue are dependent on the plant species, the plant developmental stage and concentration of application (Henke et al, 1974) and therefore, the development of this strategy for weed management systems requires the determination of which amino acids and concentrations are efficacious against the targeted weed species and whether the inhibition is reversible by other amino acids potentially present in the soil (Sands and Pilgeram, 2009). Properly implemented this strategy assumes low toxicity for plants other than the targeted weed and low persistence in the soil through microbial metabolization.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of growth and an increase in the per cent aminoacylation of methionyl-tRNA by methionine has also been demonstrated (33). Administration ofmethionine (0.25 to 0.5 mM) to other higher plants (e.g., Lemna, Zea, Hordeum) has been shown to be toxic (12,14,36 (Tables V-VII), storage protein methionine on a unit protein basis was greater in methionine-supplemented cotyledons than in immature seeds (<400 mg) because the ratio of Il S to 7S proteins was greater in supplemented cotyledons (Table II).…”
mentioning
confidence: 98%